THE RELATIONSHIP BETWEEN TERMINAL MONITORING DEVICE INSTALLATION IN RESTAURANTS AND AN INCREASE IN TAX REVENUE IN SURAKARTA FROM 2014 TO 2021 - Agustina Fati Trinitasia Laoli; Hanung Triatmoko; Asaprima Putra Kurnia; Trisninik Ratih Wulandari (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2022)
The purpose of this research is to analyze the effect of installing Terminal Monitoring Device (TMD) in restaurants on the increase in tax revenue in Surakarta City for 2014—2021, its contribution to regional taxes and Regional Original Income (Pendapatan Asli Daerah/PAD), as well as the obstacles. The method applied in this research is a descriptive quantitative approach. This research used primary and secondary data. Primary data include interviews with the Regional Revenue, Financial and Asset Management Agency (Badan Pendapatan Pengelolaan Keuangan dan Aset Daerah/BPPKAD) of Surakarta, while secondary data include reports on the realization of restaurant tax revenues, reports on the realization of regional taxes, reports on the realization of PAD, and data on the number of restaurants taxpayers in Surakarta. The results of this research show that the installation of TMD did not have a significant impact on increasing restaurant tax revenues in Surakarta City and increasing the restaurant tax contribution to regional taxes and PAD during 2018—2021. Several technical and non-technical factors cause the non-optimal installation of TMD to increase restaurant tax revenues in Surakarta.